2021
DOI: 10.3390/designs5030048
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Controlled Mechanical Ventilation Systems for Indoor Acoustic Comfort

Abstract: The indoor air quality inside living spaces is a fundamental factor in providing adequate comfort. In order to do this, a minimum air exchange must be ensured. This can be obtained by means of natural or mechanical ventilation or using the Controlled Mechanical Ventilation system (CMV). CMV ensures better energy performance, as in the winter period, the warm air that comes out of the building preheats the cold air that enters, and the opposite occurs in the summer period. A possible problem with CMV is the noi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Acoustic measurements performed on an apartment equipped with CMV operating in a single and simultaneous mode and related acoustic simulations demonstrated that, by differentiating the fan speed of the CMV, a considerable acoustic comfort improvement could be obtained in the bedrooms and in the living room/kitchen. Class I for living rooms and class I or II for bedrooms according to the EN 16798-1 standard could be achieved through speed optimization [5].…”
mentioning
confidence: 99%
“…Acoustic measurements performed on an apartment equipped with CMV operating in a single and simultaneous mode and related acoustic simulations demonstrated that, by differentiating the fan speed of the CMV, a considerable acoustic comfort improvement could be obtained in the bedrooms and in the living room/kitchen. Class I for living rooms and class I or II for bedrooms according to the EN 16798-1 standard could be achieved through speed optimization [5].…”
mentioning
confidence: 99%